2016
DOI: 10.1039/c5ob01956g
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in the alkali metal ion-templated formation of oligo(ethylene glycol)-containing [2]catenanes

Abstract: An investigation into the most suitable alkali metal ions for templating the assembly of [2]catenanes from di-, tri-, and tetra(ethylene glycol)-containing guest diamines and isophthalaldehyde has indicated that Na(+), K(+), and Rb(+) ions are optimal for preparing [2]catenanes containing at least one di(ethylene glycol) unit, two tri(ethylene glycol) units, and at least one tetra(ethylene glycol) unit [in the absence of a di(ethylene glycol) unit], respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
1
25
0
Order By: Relevance
“…Thus, we speculated that the thermodynamic macrocycle-metal binding data obtained from ITC experiments might be correlated to the kinetic phenomena in the ion-templated MCO. 33,37,39…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we speculated that the thermodynamic macrocycle-metal binding data obtained from ITC experiments might be correlated to the kinetic phenomena in the ion-templated MCO. 33,37,39…”
Section: Introductionmentioning
confidence: 99%
“…As displayed in Figure a, the 1 H NMR spectrum of an equilibrated (323 K, 160 h) equimolar (20 mM) mixture of the diamine 1 , the dialdehyde 2 , the DEG-containing macrocycle 6 , and NaTFPB {TFPB = tetrakis­[3,5-bis­(trifluoromethyl)­phenyl]­borate} (Scheme ) featured several significantly upfield shifted signals for the protons of the DEG unit of the [2]­catenanes. Considering our previous experience , and 2D COSY and NOESY spectra (see the Supporting Information), we identified the signals at δ 2.61 and 2.99 as representing the protons of the DEG unit of the interlocked imino macrocyclic component 3 in the homo[2]­catenane [ 4· Na] + and the hetero[2]­catenane [ 13· Na] + , respectively, and the signals at δ 2.46 and 2.91 as representing the DEG unit of the macrocyclic component 6 in [ 13· Na] + . Nevertheless, an intense signal at δ 3.52 in the equilibrated mixture, representing the resonances of the protons of the Na + -complexed DEG unit of the macrocycle 6 , suggested that the formation of the [2]­catenane [ 13· Na] + was not efficient under the reaction conditions.…”
Section: Results and Discussionmentioning
confidence: 99%
“…On the basis of integration of these signals, the molar ratio of the hetero[2]­catenane [ 13· Na] + , the homo[2]­catenane [ 4· Na] + , and the macrocycle [ 6· Na] + was 1.7:1.0:3.2. Using NaBH 4 to reduce the mixture formed on a larger scale, but under similar conditions, followed by Eschweiler–Clarke methylation, we isolated the hetero[2]­catenane 14 and the homo[2]­catenane 15 in yields of 14% and 7%, respectively (the recovery yield of 6 was 59%). Thus, clipping the DEG-containing imino macrocycle 3 onto the DEG-containing macrocycle 6 in the presence of templating Na + ions was not particularly selective or efficient.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We prepared the [2]rotaxane 1 , comprising the macrocyclic component 2 and the dumbbell‐shaped component 3 (Scheme ), through alkali metal ion templated clipping of an imino macrocycle and subsequent reduction . 2D COSY and NOESY experiments allowed us to identify most of the signals in the 1 H NMR spectra of the [2]rotaxane 1 in [D 8 ]toluene at 298 K (Figure , see the Supporting Information for the full signal assignments).…”
Section: Figurementioning
confidence: 99%